A prostate cancer tissue specific spectral library for targeted proteomic analysis. Issue 7 (1st December 2021) - Sun, Rui; Lyu, Mengge; Liang, Shuang; Ge, Weigang; Wang, Yingrui; Ding, Xuan; Zhang, Cheng; Zhou, Yan; Chen, Shanjun; Chen, Lirong; Guo, Tiannan
Abstract: Prostate cancer is the most common cancer in males worldwide. Mass spectrometry‐based targeted proteomics has demonstrated great potential in quantifying proteins from formalin‐fixed paraffin‐embedded (FFPE) and (fresh) frozen biopsy tissues. Here we provide a comprehensive tissue‐specific spectral library for targeted proteomic analysis of prostate tissue samples. Benign and malignant FFPE prostate tissue samples were processed into peptide samples by pressure cycling technology (PCT)‐assisted sample preparation, and fractionated with high‐pH reversed phase liquid chromatography (RPLC). Based on data‐dependent acquisition (DDA) MS analysis using a TripleTOF 6600, we built a library containing 108, 533 precursors, 84, 198 peptides and 9384 unique proteins (1% FDR). The applicability of the library was demonstrated in prostate specimens.